KEPENTINGAN INDONESIA DAN SINGAPURA DALAM PERJANJIAN EKSTRADISI TAHUN 2022 MELALUI ISI PERJANJIAN DAN PROSES RATIFIKASI - Ramadani, Anggita Dian; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study examines the interests of Indonesia and Singapore in the 2022 Extradition Treaty through the treaty’s provisions and the ratification process, particularly regarding law enforcement efforts and the repatriation of individuals convicted of corruption. After facing setbacks since 2007, the treaty was finally concluded on January 25, 2022, and ratified by Indonesia through Law No. 5 of 2023 and by Singapore through its domestic mechanisms. This study employs a descriptive qualitative method using literature review techniques and is analyzed through a two-level games perspective to examine the interplay between international negotiations and the domestic dynamics of both nations. The results of the study indicate that this agreement incorporates the principle of double criminality, limited retroactive provisions, and a more structured extradition mechanism. The differences in the legal systems, Indonesia’s civil law system and Singapore’s common law system influenced the ratification process. But did not hinder the implementation of the agreement rather they reflect the alignment of the two countries’ interests in reaching an agreement. Keywords: Extradition, Treaty, Ratification, Bilateral, National Interest